Reassessing Wheat Crises in Eighteenth-century Thessaloniki - Gounaris, Basil C. (The Historical Review/La Revue Historique, 2009)
Wheat crises and local riots in eighteenth-century Thessaloniki are not unknown to scholars. However, all the relative conclusions are based mostly on Svoronos’ and Iliadou’s indexes rather than on additional research of primary sources. Therefore, much space has been given to speculation and various issues have been left without proper examination. This paper seeks to explore, through the study of the French consular correspondence, if there was a common pattern in all wheat crises; why did not all crises develop into open revolts; and, who were the basic participants in the making and management of the crises. It asserts that the development of wheat shortages into popular riots was the outcome of local commercial interests and calculated petty politics, not of famine.